The Effectiveness of the 2022 Student Exercise Program in Improving the Physical Fitness of PGMI Students - Akbar, Andi Khemal; Mulyaningsih, Eka (Edukasi, 2025)
This study examined the effectiveness of the 2022 Student Exercise Program in improving the physical fitness of PGMI students at IAIN Bone. Employing a quantitative pre-experimental design with a one-group pretest-posttest model, a sample of 20 female students was selected from a population of 240 using random sampling. Participants underwent six sessions of rhythmic aerobic exercise. Physical fitness was assessed using a standardized test for ages 16–19, including a 60-meter sprint, pull-ups, sit-ups, vertical jump, and a 1,000-meter run. Data were analyzed using descriptive and inferential statistics. A paired sample t-test revealed a significant improvement in posttest scores (t = -9.647; p = 0.000), indicating that the program effectively enhanced students’ physical fitness. These findings support the integration of structured physical activity into higher education, particularly in teacher training programs.